Pengaruh Pola Kepemimpinan Demokratis Kepala Sekolah Terhadap Motivasi Kerja dan Kemampuan Pedagogik Guru di SDN 009 Sari Mulya - Boiman Boiman (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aims to determine the influence of the principal's democratic leadership pattern on the work motivation and pedagogical skills of teachers at SDN 009 Sari Mulya. This quantitative research approach is expected to provide a deeper understanding and interpretation of the meaning of relevant facts and reality. The study was conducted at SDN 009 Sari Mulya, Pangkalan Lesung District, Pelalawan Regency, Riau Province. A population of 10 teachers served as the research sample. Data management began with validity and reliability tests, as well as instrument hypothesis testing using SPSS version 25 for Windows. The next step was normality testing, linearity testing, and finally, hypothesis testing by conducting a simple regression test Y = α + bX to determine the functional relationship between variable X and variables Y1 and Y2. The results of the study stated that democratic leadership had a positive effect on teacher work motivation with a significance value of 0.000 (<0.05) and an influence contribution of 68.4%, furthermore, democratic leadership patterns had a positive effect on teacher pedagogical abilities with a significance value of 0.002 (<0.05) and an influence contribution of 52.9%.